PROBLEMATIKA HUKUM ASAS LEX SPECIALIS - Molou, Syafril Moh Nur S.; Ismail, Dian Ekawaty; Imran, Suwitno Yutye (Collegium Studiosum Journal, 2023)
This article aims to determine the problems of implementing article 44 paragraph (3) of the law on the elimination of domestic violence in criminal acts of domestic violence which result in the victim's death. This research uses normative legal research methods. If you look at the severity of criminal cases, what often happens are cases of domestic violence in which the victim dies. The crime of domestic violence actually has a special law that regulates criminal acts within the household locus, namely Law number 23 of 2004 concerning the elimination of domestic violence. However, sometimes there are still similar cases which are decided by applying Article 338 of the Criminal Code (KUHP).